Improved microscopy diagnosis of pulmonary teberculosis using sodium hypochlorite concentration technique in Tanga, Tanzania - Makunde, WH; Makunde, RA; Kamugisha, LM; Mgema, SG; Liwa, A (Tanzania Journal of Health Research, 2007)
No Abstract. Tanzania Health Research Bulletin Vol. 9(2) 2007: pp.87-93